Impact of Social Media Usage and Self-Esteem on Mental Health - Naeem, Iram; Naseer, Furqan (Journal of Global Social Transformation, 2025)
The excessive boom of the social media has altered how humans interact, explicit themselves and maintain relationships. Although the webweb sites provide blessings in phrases of connection, sharing of records and expression of self, mounting proof proposes that overindulgence or maybe dysfunctional use of social media can adversely have an effect on the mental fitness of the individual. Meanwhile, shallowness is an essential element that could affect how humans sense approximately themselves, react to a social comparison, and paintings with emotional problems withinside the virtual space. The paper discusses the interaction of social media use and vanity on intellectual fitness, in addition to how the developments of on line interplay and self-notion hook up with the self-view and emotional stability, stress, tension and the overall functioning of the psyche. The take a look at examines the concept of whether or not social media is a high-quality surroundings that promotes a healthful circumstance or a scenario that results in the improvement of lack of confidence and distress, mainly in human beings with low vanity. The take a look at will study how the connection among virtual conduct and private mental assets may be visible as a deeper perception into the function of the modern-day on line tradition in forming the intellectual fitness outcomes. The outcomes are in all likelihood to offer the knowledge of the mental strategies through which social media can in a different way impact human beings and emphasize the want to sell healthful on line behaviors and advantageous self-belief to beautify their intellectual fitness.